Strategic management in the system model of the corporate enterprise organizational development - Nina Avanesova; Sulaiman Tahajuddin; Olha Hetman; Yuliia Serhiienko; Vyacheslav Makedon (Agenda Publishing House Limited, 2021)
The article describes organizational and methodological components of using strategic management within a framework of corporate governance and development. The authors have formed a range of methodological provisions, regarding the choice of a marketing strategy by the corporate enterprise. They identified the main recourse flows within the framework of the used strategies. They also determined the strategic management components, required for providing efficiency of the corporations’ physical resources formation and use. They developed a graphical model for the determination of the corporation’s strategic position on the market. It was proved that a functional strategy involves a close correlation between the management and incorporated ownership relations, manifesting itself in a strategy in the field of finance of the corporation, ensuring corporation industrial stability, effective use of physical resources, the formation of the cash resources funds in the established amount, real property management and caretaking control, etc. The authors offered a methodology for conducting a strategic evaluation of the corporation in the basic market conditions.